2021
DOI: 10.1021/acs.biomac.0c01715
|View full text |Cite
|
Sign up to set email alerts
|

Transition of Conformation and Solubility in β-Sheet-Structured Poly(l-cysteine)s with Methylthio or Sulfonium Pendants

Abstract: Poly(L-cysteine)s with methylthio pendants (PMTLCs) were synthesized by ring-opening polymerization of a new L-cysteine-based Ncarboxyanhydride. The thioether bonds of PMTLC can be readily oxidized by H 2 O 2 yielding water-soluble PMTLC OX . The methylthio groups can undergo an alkylation reaction using methyl iodide and a subsequent ion-exchange reaction yielding sulfonium-based polypeptides (PPLC-DMS-X, where X = I, BF 4 ). PPLC-DMS-X showed upper critical solution temperature-type thermo-and oxidationrespo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…As shown in Figure b, it is clearly observed that the samples exhibit strong amide I and II bands at 1635 and 1525 cm –1 , respectively, indicating that the β-sheet is a predominant conformation of alkyl-P­(Cys-SS-CH 2 CH 2 COOH). This result is consistent with the fact that poly­( l -cysteine) exclusively forms a β-sheet structure. ,, It should be noted that the secondary structure of the PAs varied depending on the state of the PAs.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…As shown in Figure b, it is clearly observed that the samples exhibit strong amide I and II bands at 1635 and 1525 cm –1 , respectively, indicating that the β-sheet is a predominant conformation of alkyl-P­(Cys-SS-CH 2 CH 2 COOH). This result is consistent with the fact that poly­( l -cysteine) exclusively forms a β-sheet structure. ,, It should be noted that the secondary structure of the PAs varied depending on the state of the PAs.…”
Section: Resultssupporting
confidence: 87%
“…This result is consistent with the fact that poly(L-cysteine) exclusively forms a β-sheet structure. 22,23,39 It should be noted that the secondary structure of the PAs varied depending on the state of the PAs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, polymerizations of 𝛼-amino acid NTAs in amide polar solvents are still regarded difficult as the bimolecular termination is inevitable, whereas polar solvents such as DMF are common for NCA polymerizations. [109][110][111] Due to limited initiators and slow polymerization rates, designs of efficient catalysts and initiators for controlled polymerizations of NTAs are an intriguing topic. Moreover, the polymerizations of NTA and NNTA monomers with unprotected functional groups, especially thiol and hydroxyl groups, are rarely reported.…”
Section: Advantages and Unsettled Problemsmentioning
confidence: 99%